Inequality, Demography and Fiscal Policy - Luo, Weijie (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book aims to empirically and theoretically study how income inequality and demographic change affected fiscal policy and subsequent economic growth globally in the past decades from four perspectives. First, it briefly reviews the dynamic changes of income sources that contribute to inequality. Second, it distinguishes between income inequality induced by differences in labor productivity and income inequality induced by differences in capital income. Third, it briefly reviews the dynamic changes of tax composition in the age of demographic change. Last, it discusses the impacts of changes in age structure on the extent of taxes on income relative to expenditure. This book offers a comprehensive discussion to understand and analyze the reason, performance and challenge of fiscal policy and economic growth from the perspective of inequality and demographics. In addition to students, teachers and researchers in the areas of equity, demography, political economy and economic policy, this book is also of great interest to policy makers, planners and non-government agencies who are concerned with understanding and addressing poverty-related and aging-related issues in developed and developing countries.
Inequality and the Size of US State Government -- Inequality and Government Size: A Political Economy Theory and OECD Evidence -- Inequality and Government Debt -- Population Aging and the Composition of Taxes: A Political Economy Theory -- Population Aging and the Composition of Taxes: Evidence from International Panel Data. .
Keywords: Labor economics; Economic policy; Finance, Public; Finance; Labor Economics; Economic Policy; Public Economics; Financial Economics